Foucault, o sujeito e a sexualidade: a produção do sujeito na história da sexualidade de Michel Foucault - Hack, Rafael Fernando (2007)
The current dissertation discusses and characterizes the mecanisms and the production processes of the subject in the three works of the History of Sexuality of Michel Foucault ("The Will to know", "The Use of Pleasure" and "The Care of the Self"). It starts introduction the reader to the intellectual trajectory of the French philosopher in order to delimit the problem inside his production. In a first chapter, it characterizes and discusses the production processes of the subject that means the objectivation, the individuation and the subjectivation, for a later analyze of these processes and their respective mechanisms in the History of Sexuality. The processes of subject-constitution, present during the work of the philosopher, are discussed in an including way during the periods called: archeology (objectivation), genealogy (individuation) and ethical (subjectivation). By this way, it is an objectivation observed as the constitution of the subject as a knowledge object, and also as the individuation taken as the production of the subject through the external coercive mechanisms and the subjectivation discussed in the self-reflexive constitution of the individual, that presents himself specific mechanisms during the History of Sexuality. In the second chapter the individuation and the objectivation present in "The Will to know" is discussed. In the third and the las chapter, the discussion makes for the subjectivation present in the last two volumes of the History of Sexuality. The dissertation concludes characterizing and discussing the different production processes of the subject and its respective mechanisms during the History of Sexuality.